Jose Martin Mikelajauregi “Ezkerra” (Bera 1763- Irun 1861) Bidasoako bertsolaria - Urkizu, Patri (EGAN, 2021)
PATRI URKIZU. Jose Martin Mikelajauregi “Ezkerra” (Bera 1763 - Irun 1861) Bidasoako bertsolaria